Fuel characteristics of molasses-impregnated low-rank coal produced in a top-spray fluidized-bed reactor. Issue 9 (3rd July 2016) - Park, Jae Hyeok; Lee, Chang-Ha; Joo, Ji Bong; Bae, Dal-Hee; Shun, Dowon; Moon, Jong-Ho; Park, Young Cheol; Shin, Jong-Seon; Choi, Young-Chan; Jung, Doo-hwan; Park, Jaehyeon
ABSTRACT: Upgrading low-rank coal (LRC) through various strategies is always an important issue. Here, we report the production of hybrid coals and an evaluation of their characteristics for use as a fuel in power plants. The hybrid coals (HCKs) were prepared by a combination of drying and biomass impregnation into an Indonesian LRC followed by a precarbonization process. We used a top-spray fluidized-bed reactor for drying, biomass impregnation, and precarbonization to produce hybrid coals that have improved fuel characteristics in terms of heating value, moisture readsorption, and combustion patterns. A systematic study reveals that experimental parameters, such as a bed temperature, bioliquid spraying procedure, and precarbonization temperature strongly influence the characteristics of the resulting hybrid coal, meaning that they have an important role in upgrading LRC. In particular, the hybrid coal prepared by a process of simultaneous drying and bioliquid spraying followed by precarbonization at 200–300°C showed high contents of fixed carbon, an improved heating value, lower moisture adsorption, and single combustion patterns in which the characteristics were dramatically upgraded for practical use as a fuel in power plants. In addition, the simultaneous process using a fluidized-bed reactor has great potential because it can achieve process simplification, reduce manufacturing costs, and handle coal particles easily.